Developing of Capacity Analysis Method - Kocsi, Balázs; Budai, István (International Journal of Engineering and Management Sciences, 2016)
Capacity planning is strategic significance in companies’ life. The strategic of capacity enlarging in fluencies the competitiveness of companies. There are several method for determination of long-term capacity from simple ones to expensive, high calculation requiring processes. We have to rearrange the production for the increasing demand, it is not so simple because it needs some investments. We must scrutinize that is it worth for us? The aim of this study is to investigate whether capacity enlarging is going to be realizable without investments only the eliminate of waste. In this method needs exact determine of the current capacity so we use modified, extended capacity model. In this model we consider the availability, quality and efficiency of the machine more over we observe the effect of the service program of the machine.